Qualitätssicherung Die Praxis der Übersetzungsrevision im Zusammenhang mit EN 15038 und ISO 17100 - Schnierer, Madeleine (TRANSÜD. Arbeiten zur Theorie und Praxis des Übersetzens und Dolmetschens, 2019)
Translation revision is essential for ensuring the quality of translations. It is a service of its own, which involves the provision of additional personnel, time and financial resources. The quality standards, the auditing practice and the service providers are the focus of a study with Austrian language service providers, presented here by Madeleine Schnierer. The results describe the practical framework conditions and the current status of translation revision in Austria. They also show the extent to which EN 15038 and ISO 17100 form the basis of the respondents' professional activities. These and other revealing results demonstrate the importance of translation revision within quality assurance. Madeleine Schnierer studied translation with French and Russian at the University of Innsbruck and graduated from the University of Geneva with a PhD thesis on translation revision. Since September 2018 she is a lecturer in the German Department of the Faculty of Translation and Interpreting at the University of Geneva, where she teaches translation, translation revision and German language and cultural competence.